Drills and drilling safety - Safetycare Australia Pty. Ltd. (Australia : Safetycare Australia Pty Ltd., 1993)
Presents how to drills and drilling safety at work place to prevent any accidents
A skills education program
VCD format
Keywords: Drilling and boring; Industrial safety; Industrial accidents -- prevention; Drilling muds